Examination of orthopedic & athletic injuries 2026-02-15T18:24:09+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Starkey, Chad, 1959- (F.A. Davis Company, 2015)

(untitled)
"Perform accurate evaluations of orthopedic injuries. In this book, organized by body region, each chapter begins with a review of anatomy and joint function; proceeds through clinical examination, specific pathologies, and related selective tissue tests (specific tests); and concludes with a discussion of intervention strategies and on-field or initial management of specific conditions"--Back cover